On the interference of the weight and boundary contour for algebraic polynomials in weighted Lebesgue spaces. II - Özkartepe, P. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We continue to study the estimation of the modulus of algebraic polynomials on the boundary contour with weight function, when the contour and the weight function have certain singularities with respect to the their quasinorm in the weighted Lebesgue space. In particular, the exact estimates were obtained for polynomials orthonormal on the curve with respect to the weight function with zeros on the same curve.